Schwartz’s Values, Perceived Organizational Support (POS), and Work Engagement: The Mediating Role of Work Meaningfulness: [Schwartz’s Values, Perceived Organizational Support (POS), dan Work Engagement: Peran Mediasi dari Work Meaningfulness] - Kurniawan, Christian Kevin; Indrayanti (Faculty of Psychology, Universitas Surabaya, 2023)
Conditions of the situation after the COVID-19 pandemic have an impact on the phenomenon of employee work engagement. Employees who are accustomed to working from home are asked to adjust to the new work design such as hybrid working. By having values and perceived organizational support (POS), employees who can find work meaningfulness will have higher work engagement in any work design after the COVID-19 pandemic. This study aims to examine the role of work meaningfulness as a mediator in the relationship between perceived organizational support (POS) and values toward work engagement. The data collection was carried out online and involved 220 Indonesian employees who worked in various fields. Study participants were recruited by purposive sampling method. Instruments of this study consist of the Survey of Perceived Organizational Support (SPOS), Portrait Values Questionnaire (PVQ), The Work and Meaning Inventory (WAMI), and Utrecht Work Engagement Scale (UWES). The data analysis in this study utilized the PROCESS mediation analysis. The results showed that work meaningfulness significantly had a mediating effect on perceived organizational support (POS) toward work engagement (β = .743; p < .001). Woek meaningfulness also had a mediating effect on values toward work engagement (β = .581; p < .001). Especially for values, work meaningfulness had a significant mediating effect on self-transcendence (β = .129; p < .01), openness to change (β = .120; p < .05), and conservation (β = .220; p < .01), but has no mediation effect on self-enhancement towards work engagement (β = .108; p > .05). This result confirms that having meaningfulness experience during working would increase the role of situational factors (perceived organizational support [POS]) and individual factor (values) toward work engagement. Kondisi pasca pandemi COVID-19 berdampak pada fenomena work engagement karyawan di tempat kerja. Karyawan yang terbiasa bekerja dari rumah diminta untuk menyesuaikan diri dengan desain kerja baru yang berupa hybrid working. Dengan memiliki values dan perceived organizational support (POS), karyawan yang dapat menemukan work meaningfulness akan memiliki work engagement yang lebih tinggi pada kondisi desain kerja apapun pasca pandemi COVID-19. Studi ini bertujuan menguji peran work meaningfulness sebagai mediator dalam hubungan antara perceived organizational support (POS) dan values terhadap work engagement. Pengumpulan data studi dilakukan secara daring dengan melibatkan 220 karyawan dari berbagai bidang. Partisipan studi direkrut dengan metode purposive sampling. Pengumpulan data menggunakan Survey of Perceived Organizational Support (SPOS), Portrait Values Questionnaire (PVQ), The Work and Meaningful Inventory (WAMI), dan Utrecht Work Engagement Scale (UWES). Analisis data menggunakan uji mediasi PROCESS. Hasil studi menunjukkan bahwa work meaningfulness secara signifikan memiliki efek mediasi pada perceived organizational support (POS) terhadap work engagement (β = 0,743; p < 0,001). Work meaningfulness juga mampu memediasi hubungan antara values dan work engagement (β = 0,581; p < 0,001). Khusus untuk variable values, work meaningfulness memiliki efek mediasi pada dimensi self-trancendence (β = 0,129; p < 0,01), openness to change (β = 0,120; p < 0,05), dan conservation (β = 0,220; p < 0,01) terhadap work engagement, namun pada dimensi self-enhancement, work meaningfulness tidak memiliki efek mediasi dalam hubungan antara self-enhancement terhadap work engagement (β = 0,108; p > 0,05). Hasil tersebut mengkonfirmasi bahwa memiliki pengalaman meaningful selama bekerja dapat meningkatkan peran faktor situasional (perceived organizational support [POS]) dan faktor individual (values) terhadap work engagement.